Epidermal Renewal after Treatment of Primary Canine Hypothyroidism using Levothyroxine - Alves, Caroline Castagnara; Waller, Stefanie Bressan; Costa, Glícia Meneses; da Silva, Eduardo Gonçalves; Soares, Matheus de Azevedo; Pellegrin, Thaíssa Gomes; de Vascocellos, Amanda Leal; Costa, Paula Priscila Correia (Acta Scientiae Veterinariae, 2021)
Background: Primary canine hypothyroidism, an endocrine disorder that causes imbalances in the hypothalamus-pituitarythyroid axis, is a common cause of endocrine dermatoses, which frequently presents with opaque dry brittle hair. Tissue changes are also visible, such as myxedema, hyperkeratosis, epidermal atrophy, alopecia, and others. This paper describes the skin changes caused by primary hypothyroidism in a female dog before and after treatment with levothyroxine. Case: This case study involved a 7-year-old Dalmatian bitch with a history of weight gain and changes such as rough dry brittle hair. For about a year, the dog also had also presented symmetrical erythematous and alopecia skin lesions in the regions of the hind limbs, lower back and tail, progressive lethargy and fatigue after exercise. A hemogram showed mild normocytic and normochromic regenerative anemia, as well as mild leukopenia and neutropenia. Biochemical tests revealed increased levels of creatinine, total cholesterol, and triglycerides. Skin biopsy revealed the presence of comedones in the epidermis and acanthosis and trichilemmal keratinization. Hormonal tests revealed high TSH and low free T4 and total T4 levels. A cervical ultrasound scan showed changes in the thyroid glands, with hypoechoic parenchyma, in addition to increased size of the right lobe, suggesting thyroiditis. Based on these exams, the patient was diagnosed with primary hypothyroidism, and treatment with levothyroxine was instituted. Discussion: Around 90% of dogs with hypothyroidism show a decrease in total T4 and about 65-75% of them show an increase in TSH levels. In endocrinopathy, there is a decrease in the expression of T3 receptors in the keratinocytes and genes responsible for epidermal renewal. Also, molecules that affect epidermal differentiation bind to intracellular receptors belonging to the steroid/thyroid hormone superfamily. In this study, however, the application of the minimum levothyroxine dose restored the normal epidermal pattern for the species and the remaining parameters returned to normal. The hormone T3 acts in the differentiation of keratinocytes, a fact that, although not yet proven, is believed to be indirect and mediated by the epidermal growth factor or by the expression of the genes responsible for the renewal of the epidermis. Besides, some effects on the epidermis caused by deficiency of thyroid hormones may be due to secondary vitamin A deficiency, which is necessary for epithelial differentiation and binding epidermal growth factor (EGF) to the cell. Still, there is a theory that sex hormones also affect the differentiation of the epidermis, as studies show that deficiency causes effects similar to those caused by hypothyroidism. Some studies indicate the investigation of the relationship between secondary vitamin D deficiency and the increased cellularity of the epidermis of the spayed hypothyroid female rats. Additionally, the mechanism of the formation of hyperkeratosis in hypothyroidism is not yet elucidated. T3 is known to regulate keratin gene expression and perhaps also epidermal maturation, epithelial cycle, and normal keratin synthesis. The single treatment with levothyroxine in the female dog was effective in promoting the restoration of gene expression to T3 in keratinocytes. Keywords: dermatopathies, endocrinopathies, hypothyroidism, levothyroxine, synthetic hormone.